2020
DOI: 10.1016/j.xcrm.2020.100138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Network Analysis Reveals Altered Bile Acid Synthesis and Metabolism in Alzheimer’s Disease

Abstract: Summary Increasing evidence suggests Alzheimer's disease (AD) pathophysiology is influenced by primary and secondary bile acids, the end product of cholesterol metabolism. We analyze 2,114 post-mortem brain transcriptomes and identify genes in the alternative bile acid synthesis pathway to be expressed in the brain. A targeted metabolomic analysis of primary and secondary bile acids measured from post-mortem brain samples of 111 individuals supports these results. Our metabolic network analysis sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 83 publications
6
148
0
Order By: Relevance
“…In a recent publication using brain tissue samples from the BLSA included in this study, we reported higher concentrations of the primary bile acids, cholic acid, and chenodeoxycholic acid in AD samples relative to CN 56 . In addition, a study using similar iMAT-based analysis identified significant differences between AD and CN in bile acid-associated reactions using transcriptomic data across multiple cohorts and identified HSD3B7 as significantly altered in AD 57 . Together, these results point to a shift in cholesterol catabolism toward the enhanced synthesis of bile acids in AD and an accompanying reduction in 24S-hydroxycholesterol levels that may compromise synaptic plasticity and accelerate cognitive impairment through perturbation of NMDA receptor activity 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication using brain tissue samples from the BLSA included in this study, we reported higher concentrations of the primary bile acids, cholic acid, and chenodeoxycholic acid in AD samples relative to CN 56 . In addition, a study using similar iMAT-based analysis identified significant differences between AD and CN in bile acid-associated reactions using transcriptomic data across multiple cohorts and identified HSD3B7 as significantly altered in AD 57 . Together, these results point to a shift in cholesterol catabolism toward the enhanced synthesis of bile acids in AD and an accompanying reduction in 24S-hydroxycholesterol levels that may compromise synaptic plasticity and accelerate cognitive impairment through perturbation of NMDA receptor activity 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The group and region-specific binary vectors were then compared using the Fisher Exact Test to determine whether the activity of reactions (active or inactive) were significantly ( P < 0.05) altered between AD and CN (Fig. 3b [8]) 57 . We indicated significant results in the hippocampus and ERC as well as the visual cortex (control region).…”
Section: Methodsmentioning
confidence: 99%
“…Additional details are provided in the index paper [20]. We identified BA receptor genes (including receptors involved in BA homeostasis) using a literature search [22][23][24] and include the full list in S2 Table.…”
Section: Study Participantsmentioning
confidence: 99%
“…Particularly, several oxylipins of the acute in ammation pathway were reportedly elevated in AD (14,15) and pro-resolving (quenching activated in ammatory signal) lipid mediators have been suggested as potential treatment for AD (16). Speci c changes in bile acids metabolism, including a decrease in primary and an increase in secondary metabolites were also observed in AD subjects (17) and differences in bile acids clearance for cholesterol pathway were reported in AD (18). Notably, bile acids and some steroids manifest neuroprotective functions through activation of steroid receptors (19).…”
Section: Introductionmentioning
confidence: 98%